Exploring fintech adoption in cashless transactions: Evidence from the bank for investment and development of Vietnam - Linh, Vu Thuy; Hai, Tran Van (The Economics and Finance Letters, 2025)
In the era of Industry 4.0 and ongoing digital transformation in the banking sector, Fintech has become a vital catalyst for the growth of cashless payment services in Vietnamese commercial banks. The Bank for Investment and Development of Vietnam (BIDV) is among the leading banks at the forefront of Fintech adoption, aiming to improve customer experience and enhance the efficiency of electronic transactions. However, the extent of Fintech adoption varies significantly across BIDV branches and is influenced by various factors. Grounded in theoretical foundations and a comprehensive review of previous studies, this research develops a conceptual model to identify the main factors affecting the level of Fintech adoption in cashless payments at BIDV. Primary data were collected through a structured survey of 250 customers across multiple BIDV branches. The data were analyzed using SPSS software, beginning with reliability testing to confirm the consistency of measurement scales. Subsequently, exploratory factor analysis (EFA) was employed to uncover the underlying factor structure, followed by multiple regression analysis to assess the impact of each factor on Fintech adoption levels. The results indicate that all identified factors have a positive and statistically significant influence on the degree of Fintech adoption across BIDV branches. Based on these findings, the study offers several practical recommendations to promote more effective and consistent Fintech implementation. The main contribution of this research lies in providing empirical evidence and a validated analytical framework for understanding the key drivers of Fintech adoption within Vietnamese commercial banking.